If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 3n = -7 Solving -6 + 3n = -7 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3n = -7 + 6 Combine like terms: -6 + 6 = 0 0 + 3n = -7 + 6 3n = -7 + 6 Combine like terms: -7 + 6 = -1 3n = -1 Divide each side by '3'. n = -0.3333333333 Simplifying n = -0.3333333333
| 4x+2=6+4x | | 10+d=200 | | -27=6y | | 6y+5=2y+7 | | 25n^2-20n=1 | | 10x-4=11+9x | | -6=z/4 | | x-0.7=8.86 | | 4x-(9-3x)=8x-men | | -13+x=54 | | (X+3)(X+9)=0 | | 2a/3-4-3=-2/3 | | -19p=-57 | | -(k+5)=-6k | | -222=-6x-6(x+25) | | 4x=2+8x | | 35/6+x=7 | | 6x^2-17x+13=20x^12-32 | | 9+4+x=8+5 | | 12x+10+y=180 | | 7x+3=8x+9 | | b^2+16b+64=7 | | X^2-10x+1=23 | | 2(7+6x)=34+8x | | 7x-2(5x-20)=61 | | 5-2n=12 | | -4/.5=c | | 10x-8x=30 | | 6p-12=-8+7p | | 8(7p-6)= | | 4s-8=8+8s | | (4b+3)(b-12)= |